Metode Jigsaw dan Penerapannya di Dalam Kelas - Suprihati, Wahyu (Veritas Lux Mea (Jurnal Teologi dan Pendidikan Kristen), 2021)
The jigsaw method is one of the methods in cooperative learning. The jigsaw method was developed by Elliot Aronson and his colleagues from the University of Texas, then adapted by Robert Slavin and colleagues. The application of the jigsaw method in the classroom is to train students to learn to be responsible and work together, meaning that students do not only focus on themselves, but on one another. On the other hand, students learn to understand the material, on the other hand, students learn to socialize by teaching their friends who do not understand. Using descriptive qualitative methods with a literature study approach, it can be concluded that: Teachers have a big role and responsibility in carrying out learning activities with this method. The success and failure of learning activities, depending on the readiness and hard work of teachers in controlling and guiding the implementation of learning. If everything is packaged and presented properly, then the results are good.Abstrak Metode jigsaw merupakan salah satu metode dalam pembelajaran kooperatif. Metode jigsaw dikembangkan oleh Elliot Aronson dan kawan-kawan dari Universitas Texas, kemudian diadaptasi oleh Robert Slavin dan kawan-kawan Penerapan Metode jigsaw di dalam kelas adalah untuk melatih siswa belajar bertanggung jawab dan bekerja sama artinya bahwa siswa tidak hanya fokus pada dirinya sendiri, disatu sisi siswa belajar memahami materi disisi lain siswa belajar bersosialisasi dengan cara mengajarkan temannya yang belum mengerti.mengunkan metode kualitatif deskritif dengan pendekatan studi literature maka dapat disimpulkan bahwa:  Guru mempunyai peran dan tanggung jawab yang besar dalam melaksanakan kegiatan pembelajaran dengan metode ini. Keberhasilan dan kegagalan kegiatan pembelajaran, tergantung pada kesiapan dan kerja keras pengajar dalam mengendalikan serta membimbing pelaksanaan pembelajaran. Jika semua dikemas dan disajikan dengan baik, maka hasilnya pun baik.